2018
DOI: 10.1137/17m1136304
|View full text |Cite
|
Sign up to set email alerts
|

An Iterative Wiener--Hopf Method for Triangular Matrix Functions with Exponential Factors

Abstract: Abstract. This paper introduces a new method for constructing approximate solutions to a class of Wiener-Hopf equations. This is particularly useful since exact solutions of this class of Wiener-Hopf equations, at the moment, cannot be obtained. The proposed method could be considered as a generalisation of the pole removal technique. The error in the approximation can be explicitly estimated, and by a sufficient number of iterations could be made arbitrary small. Typically only a few iterations are required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…This is unlike other methods such as rational approximation and "pole removal" rely on taking non-zero imaginary part in k 0 . In this paper we also found that the results converge faster for large |k 0 | (which is equivalent to larger L) as was is found in (Kisil 2017).…”
Section: Convergencesupporting
confidence: 82%
See 4 more Smart Citations
“…This is unlike other methods such as rational approximation and "pole removal" rely on taking non-zero imaginary part in k 0 . In this paper we also found that the results converge faster for large |k 0 | (which is equivalent to larger L) as was is found in (Kisil 2017).…”
Section: Convergencesupporting
confidence: 82%
“…In the case when k 0 has a small imaginary part the convergence analysis follows almost unchanged as in (Kisil 2017). This gives that convergence occurs for large enough |k 0 |, and is faster the larger |k 0 | is.…”
Section: Convergencementioning
confidence: 84%
See 3 more Smart Citations